2023
DOI: 10.1021/acsestengg.3c00207
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Cupric Single Atom Alloy Catalysts for Electrochemical Nitrate Reduction: An Ab Initio Study

Srishti Gupta,
Daniel J. Rivera,
Matthew Shaffer
et al.

Abstract: Electrochemical nitrate reduction (E-NRR) powered by renewable electricity is a sustainable method of converting toxic nitrate into benign products (N 2 ) or value-added products (NH 3 ). Recently, single atom substitutions of Pd and Ru in inexpensive Cu have shown high activity and selectivity of E-NRR over hydrogen evolution and toward the desired product. Here, we investigate the E-NRR pathway of nine single atom substitutions in Cu to understand the relationship between single atom identity and the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…The activities of these three substances depend on the adsorption energy for NO 3 – and the preference for Cu or individual atoms for *N adsorption. This conclusion was confirmed in another similar study, in which the adsorption preference of Cu or individual atoms for *N was correlated with the d-band center of the SAAs and the position of the Cu matrix. Zhang et al reported an Fe/Cu diatomic catalyst (N 2 Fe-CuN 2 ) in which the bimetallic sites combine to form a dimer between two metal atoms, which enhances NO 3 – adsorption, while also reducing the whole energy barrier for reduction from NO 3 – to NH 3 .…”
Section: Rational Selection and Design Of Electrocatalyst Materialssupporting
confidence: 64%
“…The activities of these three substances depend on the adsorption energy for NO 3 – and the preference for Cu or individual atoms for *N adsorption. This conclusion was confirmed in another similar study, in which the adsorption preference of Cu or individual atoms for *N was correlated with the d-band center of the SAAs and the position of the Cu matrix. Zhang et al reported an Fe/Cu diatomic catalyst (N 2 Fe-CuN 2 ) in which the bimetallic sites combine to form a dimer between two metal atoms, which enhances NO 3 – adsorption, while also reducing the whole energy barrier for reduction from NO 3 – to NH 3 .…”
Section: Rational Selection and Design Of Electrocatalyst Materialssupporting
confidence: 64%